x - 3x(x)-3x(6) = 2x-9
x - 3x^2-18x = 2x-9
-17x - 3x^2 = 2x-9
*Set the equation to "0" - add 9 to both sides (when you move a term to the opposite side, always use the opposite sign).
-17x - 3x^2+9 = 2x-9+9
-17x - 3x^2+9 = 2x (subtract 2x from both sides).
-17x - 3x^2+9-2x = 2x-2x
-19x - 3x^2+9 = 0
- 3x^2-19x+9 = 0
3x^2+19x-9 = 0
First: use the Quadratic Formula which, is....
x = [-b +/- V`b^2 - 4ac] / 2a
Sec: substitute the terms with the corresponding variables... a = 3; b = 19; c = -9
x = [-19 +/- V`19^2 - 4(3)(-9)] / 2(3)
x = [-19 +/- V`19*19 - 4(3)(-9)] / 6
x = [-19 +/- V`361 - 12(-9)] / 6
x = [-19 +/- V`361 - (-108)] / 6
x = [-19 +/- V`361 + 108] / 6
x = [-19 +/- V`469] / 6
P.S. the solution doesn't need to be in decimal form, unless your teachers asks you to do so.
2007-06-13 15:31:29
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
2⤊
0⤋
x - 3x(x + 6) = 2x - 9
x - 3x² - 18x = 2x - 9
Subtract 2x - 9 from both sides
- 3x² - 19x + 9 = 0
multiply thru by -1
3x² + 19x - 9 = 0
Solve with quadratic formula
x = (-b ± â(b² - 4ac))/2a
x = (-19 ± â(361 + 108))/6
x = (-19 ± â469)/6
x = (-19 ± 21.66)/6
x = 0.4427, x=-6.777
.
2007-06-13 14:59:22
·
answer #2
·
answered by Robert L 7
·
0⤊
0⤋
x-3x(x+6) = 2x-9
x - 3x^2 - 18x = 2x - 9
-3x^2 - 19x + 9 = 0
Use quadratic formula:
(19 +/- sqrt(19^2 - 4*(-3)*(9))) / 2(-3)
(19 +/- 21.656) / -6
=0.443 or -6.776
2007-06-13 14:52:20
·
answer #3
·
answered by yeeeehaw 5
·
0⤊
0⤋
x - 3x^2-18x = 2x - 9
-3x^2 + 19x = -9
-3x^2 + 19x + 9 = 0
Use quadratic formula now, since you can't factor that.
x = -b +- sqrt (b^2 - 4ac) / 2a
= -19 +- sqrt (19^2 - 4(-3)(9))/-6
= -19 +- sqrt (361+108)/-6
= -19 +- 21.65 /-6
Root 1:
x= -0.44
Root 2:
x= 6.77
2007-06-13 14:48:29
·
answer #4
·
answered by de4th 4
·
0⤊
2⤋
im not so good at math but ill give it a try
x=-15
2007-06-13 14:56:02
·
answer #5
·
answered by dogg 2
·
0⤊
2⤋
Why should I?
2007-06-13 14:47:42
·
answer #6
·
answered by Bob Thompson 7
·
0⤊
5⤋